Nature of gallium focused ion beam induced phase transformation in 316L austenitic stainless steel. (November 2016) - Babu, R. Prasath; Irukuvarghula, S.; Harte, A.; Preuss, M.
Abstract: The microstructural evolution and chemistry of the ferrite phase ( α ), which transforms from the parent austenite phase ( γ ) of 316L stainless steel during gallium (Ga) ion beam implantation in Focused Ion Beam (FIB) instrument was systematically studied as a function of Ga + ion dose and γ grain orientations. The propensity for initiation of γ  →  α phase transformation was observed to be strongly dependent on the orientation of the γ grain with respect to the ion beam direction and correlates well with the ion channelling differences in the γ orientations studied. Several α variants formed within a single γ orientation and the sputtering rate of the material, after the γ  →  α transformation, is governed by the orientation of α variants. With increased ion dose, there is an evolution of orientation of the α variants towards a variant of higher Ga + channelling. Unique topographical features were observed within each specific γ orientation that can be attributed to the orientation of defects formed during the ion implantation. In most cases, γ and α were related by either Kurdjumov-Sachs (KS) or Nishiyama-Wassermann (NW) orientation relationship (OR) while in few, no known OR's were identified. While our results are consistent with gallium enrichment being the cause for the γ  →  α phase transformation, some observations also suggest that the strain associated with the presence of gallium atoms in the lattice has a far field stress effect that promotes the phase transformation ahead of gallium penetration. Graphical abstract: